2018
DOI: 10.1093/jac/dky360
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a diagnostics-driven antifungal stewardship programme in a UK tertiary referral teaching hospital

Abstract: The AFS programme was successful in reducing the number of inappropriate initiations of antifungals by 90%. Concurrently, mortality due to invasive candidosis was reduced by 58%. BDG testing can guide safe cessation of antifungals in ICU patients at risk of invasive candidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 27 publications
1
57
1
Order By: Relevance
“…8,23 However, no report has yet shown that antifungal stewardship improves clinical outcomes, including mortality. 24 Further, few studies have evaluated the clinical effects of an antifungal stewardship intervention using βDG testing, 12 which is useful for ruling out invasive candidemia. 11 Here, we was significantly reduced after intervention, although oral antifungal consumption, which was not a target of our daily review, was slightly but significantly increased after the intervention, resulting in an annual saving in the total cost of antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,23 However, no report has yet shown that antifungal stewardship improves clinical outcomes, including mortality. 24 Further, few studies have evaluated the clinical effects of an antifungal stewardship intervention using βDG testing, 12 which is useful for ruling out invasive candidemia. 11 Here, we was significantly reduced after intervention, although oral antifungal consumption, which was not a target of our daily review, was slightly but significantly increased after the intervention, resulting in an annual saving in the total cost of antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the situation with antimicrobial stewardship programmes, however, data on antifungal stewardship programmes are limited. 11 However, few studies have evaluated the clinical effects of an antifungal stewardship intervention using βDG testing, 12 indicating that further study is needed. [6][7][8][9] Taur et al reported that delays in treatment are associated with increased mortality in patients with Candida bloodstream infection.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 1 more Smart Citation
“…[81][82][83][84][85][86][87] Similar findings have been observed with RDTs and ASPs for fungal infections. [88][89][90] Currently, the greatest challenge to ICU clinicians is effective management of multidrug-resistant GNB infections. 79 IIAT of serious GNB infections is associated with increased mortality and has been the rationale for using broad-spectrum antibiotics upfront in critically ill patients.…”
Section: Evidence In Support Of the Use Of Rdts To Optimize Antibiotimentioning
confidence: 99%
“…Even in colonized patients, susceptibility patterns might change over time, especially in immunocompromised hosts [8]. Although the AFS has known short-term effects (e.g., reduction in antifungal consumption, costs and outcomes) on the management of IFDs and patient safety [38][39][40][41], its long-term effects has been described on resistance patterns [42]. Based on stewardship program metrics, change in resistance patterns, and pathogen-speci c resistance is the most di cult target to reach [34].…”
Section: Comparison Of the Mean Minimum Inhibitory Concentration (Micmentioning
confidence: 99%